Pathology quick review and MCQs - Mohan, Harsh
Fourth Edition of Pathology Quick Review and MCQs is abridged version of Textbook of Pathology (Seventh Edition, 2015) by the same author and includes essential aspects of pathology for users desiring to revise the subject in a short time